Pemberian Nutrisi Enteral sebagai Kontrol Glikemik pada Pasien Kritis di Unit Perawatan Intensif - Firman Dwi Cahyo; Cecep Eli Kosasih; Ristina Mirwanti (Jurnal Keperawatan Silampari, 2021)
This study aims to determine how to provide nutrition that effectively maintains the balance of blood glucose levels and glycemic control. This study uses a narrative literature review method by entering keywords into the Pubmed, Science Direct, CINAHL, Wiley, and ProQuest databases. The results showed that from the search results of 569 articles and obtained ten relevant and qualified pieces, then extracted using the DSVIA method. Provision of nutrition with the continuous method can lower the average blood glucose or reduce the incidence of hyperglycemia. Then the intermittent process significantly reduces hypoglycemia during the meal period, prevents hypoglycemia during the fasting period, and can reduce insulin requirements. In conclusion, enteral nutrition needs to be modified so that nutrition and insulin administration time can be practical and effective in controlling critical sugar levels. Keywords: Bolus Feeding, Continuous Feeding, Blood Glucose, Intermittent Feeding, Enteral Nutrition